Hepatic hydatidosis: Disease due to persistence of the parasitic chamber - Davezac, Víctor; Delgado, Bolívar; Salisbury, Siul; Folle, Enrique (Cirugía del Uruguay, 1991)
The author presents a case of post-drainage seque/ar disease of a hepatic hydatic cyst open into biliar viae and makes sorne considerations on the convenience of cystectomy as compared to other procedures in the treatment of this disease.